2021
DOI: 10.1002/path.5665
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of guanosine monophosphate synthetase (GMPS) blocks glutamine metabolism and prostate cancer growth

Abstract: Glutamine is a critical nutrient in cancer; however, its contribution to purine metabolism in prostate cancer has not previously been determined. Guanosine monophosphate synthetase (GMPS) acts in the de novo purine biosynthesis pathway, utilizing a glutamine amide to synthesize the guanine nucleotide. This study demonstrates that GMPS mRNA expression correlates with Gleason score in prostate cancer samples, while high GMPS expression was associated with decreased rates of overall and disease/progression‐free s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We found some features that can distinguish multiple cancer types with high impacts (passed counts >= 100). For example, the feature GO:0019002 (GMP binding) can classify BRCA, COADREAD, KIRC and OV, which is expected because GMP is the pharmacological target for treating multiple types of cancers ( 53 55 ). Another GO term group that can be used to classify multiple cancer type contains two GO terms, namely, GO:0031049 (programmed DNA elimination) and GO:0031052 (programmed DNA elimination by chromosome breakage), which are also involved in oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We found some features that can distinguish multiple cancer types with high impacts (passed counts >= 100). For example, the feature GO:0019002 (GMP binding) can classify BRCA, COADREAD, KIRC and OV, which is expected because GMP is the pharmacological target for treating multiple types of cancers ( 53 55 ). Another GO term group that can be used to classify multiple cancer type contains two GO terms, namely, GO:0031049 (programmed DNA elimination) and GO:0031052 (programmed DNA elimination by chromosome breakage), which are also involved in oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Its cancer-promoting effect and mechanism in HCC have also been widely studied [ 45 , 46 ]. A recent report showed that the inhibition of GMPS could block glutamine metabolism and the growth of prostate cancer [ 47 ]. Kerstin Holzer et al revealed that GMPS was a target for p53 inhibition in hepatocellular carcinoma by proteomic analysis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also being tested in other cancer types [ 30 ]. Another recent study revealed that the inhibition of guanosine monophosphate synthetase, which uses glutamine as a source of nitrogen to synthesise guanine, decreased the tumour growth in PC-3 xenograft models [ 31 ].…”
Section: Discussionmentioning
confidence: 99%